Consumer Buying Behavior in High-Tech Product Markets : An Empirical Study on Analog Wrist Watches from the Bangladeshi Perspective - Rashel, Abu; Ahmed, Faruk; Lee, Seonsu (Indian Journal of Marketing, 2017)
The aim of this paper was to measure the effects of product attributes on satisfaction through the consumer perceived value of using an analog wrist watch in the perspective of Bangladesh. In this study, a group of young generation respondents was considered as a population. Cluster and simple random sampling techniques were employed to achieve the representativeness of the population. A sample of 294 educated young people from Dhaka city was surveyed. According to the results of the study, all the factors excluding physical benefits had a significant positive effect on satisfaction through customer perceived value. These relationships suggested that there was a partial or a full mediating effect of customer perceived value on the relationship between product attributes and customer satisfaction. In addition, the gender of analog wrist users moderated the path between customer perceived value and customer satisfaction; however, the moderating effect of men users was greater than that of women users.